Hesperidin - loaded PVA/alginate hydrogel: targeting NFκB/iNOS/COX-2/TNF-α inflammatory signaling pathway - Kodous, Ahmad S.; Abdel-Maksoud, Mostafa A.; El-Tayeb, Mohamed A.; Al-Sherif, Diana A.; Mohamed, Suzan Shawky Abuelkasem; Ghobashy, Mohamed Mohamady; Emad, Ayat M.; Abd El‐Halim, Shady M.; Hagras, Soheir A. A.; Mani, Samson; Rao, Arunagiri Kuha Deva Magendhra; Hussein, Ahmed M.; et al. (Frontiers in Immunology, 2024)
Introduction Skin injuries represent a prevalent form of physical trauma, necessitating effective therapeutic strategies to expedite the wound healing process. Hesperidin, a bioflavonoid naturally occurring in citrus fruits, exhibits a range of pharmacological attributes, including antimicrobial, antioxidant, anti-inflammatory, anticoagulant, and analgesic properties. The main objective of the study was to formulate a hydrogel with the intention of addressing skin conditions, particularly wound healing. Methods This research introduces a methodology for the fabrication of a membrane composed of a Polyvinyl alcohol - Sodium Alginate (PVA/A) blend, along with the inclusion of an anti-inflammatory agent, Hesperidin (H), which exhibits promising wound healing capabilities. A uniform layer of a homogeneous solution comprising PVA/A was cast. The process of crosslinking and the enhancement of hydrogel characteristics were achieved through the application of gamma irradiation at a dosage of 30 kGy. The membrane was immersed in a Hesperidin (H) solution, facilitating the permeation and absorption of the drug. The resultant system is designed to deliver H in a controlled and sustained manner, which is crucial for promoting efficient wound healing. The obtained PVA/AH hydrogel was evaluated for cytotoxicity, antioxidant and free radical scavenging activities, anti-inflammatory and membrane stability effect. In addition, its action on oxidative stress, and inflammatory markers was evaluated on BJ-1 human normal skin cell line. Results and Discussion We determined the effect of radical scavenging activity PVA/A (49 %) and PVA/AH (87%), the inhibition of Human red blood cell membrane hemolysis by PVA/AH (81.97 and 84.34 %), hypotonicity (83.68 and 76.48 %) and protein denaturation (83.17 and 85.8 %) as compared to 250 μg/ml diclofenac (Dic.) and aspirin (Asp.), respectively. Furthermore, gene expression analysis revealed an increased expression of genes associated with anti-oxidant and anti-inflammatory properties and downregulated TNFα, NFκB, iNOS, and COX2 by 67, 52, 58 and 60%, respectively, by PVA/AH hydrogel compared to LPS-stimulated BJ-1 cells. The advantages associated with Hesperidin can be ascribed to its antioxidant and anti-inflammatory attributes. The incorporation of Hesperidin into hydrogels offers promise for the development of a novel, secure, and efficient strategy for wound healing. This innovative approach holds potential as a solution for wound healing, capitalizing on the collaborative qualities of PVA/AH and gamma irradiation, which can be combined to establish a drug delivery platform for Hesperidin.